2020
DOI: 10.1177/2050313x20944306
|View full text |Cite
|
Sign up to set email alerts
|

Different retinopathy of prematurity severity and outcomes in triplets: A case report

Abstract: In this case report, we discuss the presentation of retinopathy of prematurity in triplets born at 25 + 3 weeks gestational age of whom each had a different birth weight, weight gain and treatment requirements. Triplet A weighed 800 g and his retinopathy of prematurity had resolved with no intervention. Triplet B weighed 630 g at birth and he required bilateral intravitreal ranibizumab injection at 32 + 6 weeks. Triplet C weighed 520 g and required bilateral intravitreal ranibizumab injection at 36 weeks, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The severity of ROP may differ among babies born at the same gestational age and even among babies born out of the same pregnancy. Amro et al 7 reported a case of three triplets who presented for timely evaluation and were detected with differential retinopathies. The first kid’s retinopathy resolved with no intervention, the second kid required intravitreal ranibizumab, and the third kid required a bilateral diode laser.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of ROP may differ among babies born at the same gestational age and even among babies born out of the same pregnancy. Amro et al 7 reported a case of three triplets who presented for timely evaluation and were detected with differential retinopathies. The first kid’s retinopathy resolved with no intervention, the second kid required intravitreal ranibizumab, and the third kid required a bilateral diode laser.…”
Section: Introductionmentioning
confidence: 99%